Computed tomography for diagnosis of acute appendicitis in adults - Rud, Bo (Cochrane Database Syst Rev, 2019)
BACKGROUND: Diagnosing acute appendicitis (appendicitis) based on clinical evaluation, blood testing, and urinalysis can be difficult. Therefore, in persons with suspected appendicitis, abdominopelvic computed tomography (CT) is often used as an add‐on test following the initial evaluation to reduce remaining diagnostic uncertainty. The aim of using CT is to assist the clinician in discriminating between persons who need surgery with appendicectomy and persons who do not. OBJECTIVES: Primary objective Our primary objective was to evaluate the accuracy of CT for diagnosing appendicitis in adults with suspected appendicitis. Secondary objectives Our secondary objectives were to compare the accuracy of contrast‐enhanced versus non‐contrast‐enhanced CT, to compare the accuracy of low‐dose versus standard‐dose CT, and to explore the influence of CT‐scanner generation, radiologist experience, degree of clinical suspicion of appendicitis, and aspects of methodological quality on diagnostic accuracy. SEARCH METHODS: We searched MEDLINE, Embase, and Science Citation Index until 16 June 2017. We also searched references lists. We did not exclude studies on the basis of language or publication status. SELECTION CRITERIA: We included prospective studies that compared results of CT versus outcomes of a reference standard in adults (> 14 years of age) with suspected appendicitis. We excluded studies recruiting only pregnant women; studies in persons with abdominal pain at any location and with no particular suspicion of appendicitis; studies in which all participants had undergone ultrasonography (US) before CT and the decision to perform CT depended on the US outcome; studies using a case‐control design; studies with fewer than 10 participants; and studies that did not report the numbers of true‐positives, false‐positives, false‐negatives, and true‐negatives. Two review authors independently screened and selected studies for inclusion. DATA COLLECTION AND ANALYSIS: Two review authors independently collected the data from each study and evaluated methodological quality according to the Quality Assessment of Studies of Diagnostic Accuracy ‐ Revised (QUADAS‐2) tool. We used the bivariate random‐effects model to obtain summary estimates of sensitivity and specificity. MAIN RESULTS: We identified 64 studies including 71 separate study populations with a total of 10,280 participants (4583 with and 5697 without acute appendicitis). Estimates of sensitivity ranged from 0.72 to 1.0 and estimates of specificity ranged from 0.5 to 1.0 across the 71 study populations. Summary sensitivity was 0.95 (95% confidence interval (CI) 0.93 to 0.96), and summary specificity was 0.94 (95% CI 0.92 to 0.95). At the median prevalence of appendicitis (0.43), the probability of having appendicitis following a positive CT result was 0.92 (95% CI 0.90 to 0.94), and the probability of having appendicitis following a negative CT result was 0.04 (95% CI 0.03 to 0.05). In subgroup analyses according to contrast enhancement, summary sensitivity was higher for CT with intravenous contrast (0.96, 95% CI 0.92 to 0.98), CT with rectal contrast (0.97, 95% CI 0.93 to 0.99), and CT with intravenous and oral contrast enhancement (0.96, 95% CI 0.93 to 0.98) than for unenhanced CT (0.91, 95% CI 0.87 to 0.93). Summary sensitivity of CT with oral contrast enhancement (0.89, 95% CI 0.81 to 0.94) and unenhanced CT was similar. Results show practically no differences in summary specificity, which varied from 0.93 (95% CI 0.90 to 0.95) to 0.95 (95% CI 0.90 to 0.98) between subgroups. Summary sensitivity for low‐dose CT (0.94, 95% 0.90 to 0.97) was similar to summary sensitivity for standard‐dose or unspecified‐dose CT (0.95, 95% 0.93 to 0.96); summary specificity did not differ between low‐dose and standard‐dose or unspecified‐dose CT. No studies had high methodological quality as evaluated by the QUADAS‐2 tool. Major methodological problems were poor reference standards and partial verification primarily due to inadequate and incomplete follow‐up in persons who did not have surgery. AUTHORS' CONCLUSIONS: The sensitivity and specificity of CT for diagnosing appendicitis in adults are high. Unenhanced standard‐dose CT appears to have lower sensitivity than standard‐dose CT with intravenous, rectal, or oral and intravenous contrast enhancement. Use of different types of contrast enhancement or no enhancement does not appear to affect specificity. Differences in sensitivity and specificity between low‐dose and standard‐dose CT appear to be negligible. The results of this review should be interpreted with caution for two reasons. First, these results are based on studies of low methodological quality. Second, the comparisons between types of contrast enhancement and radiation dose may be unreliable because they are based on indirect comparisons that may be confounded by other factors.